A descriptive study of the impact of intrinsic and extrinsic factors on the career paths of clinical nutrition managers - Bange, Jennifer (Kansas State University, 2014)
Registered Dietitians (RDs) attribute the success of their careers to a variety of factors, including formal education, influential mentors, specific skill sets, flexibility, and even having a supportive spouse. RDs with strong management skills are increasingly in demand in order to coordinate nutrition care and services in a cost effective manner. Clinical Nutrition Managers (CNMs) specifically coordinate medical nutrition therapy across the continuum of patient care. To aid in the career development of CNMs, research is necessary to determine the factors that have positive and negative effects on their career paths. This study examined intrinsic and extrinsic factors that impact the career paths of CNMs in addition to perceived career satisfaction. A five-part online survey was disseminated to members of the Clinical Nutrition Management Dietetic Practice Group (CNM DPG). CNMs were also defined as RDs who coordinate medical nutrition therapy and who manage personnel, finances, or both. Results (n=146) of both quantitative and qualitative analyses identified key intrinsic factors that demonstrated a positive effect on CNMs’ career paths including self-motivation, communication skills, teamwork, and leadership skills. The study also examined CNMs’ perceptions about the extrinsic factors on their career paths. Support from upper-level management and administration was identified as a crucial factor in career advancement. Having support from family was shown to be a positive influence, while many CNMs also reported that family needs and expectations, unforeseen life circumstances, and the economic climate had limited their career paths. Social service motivation had a slightly positive influence on career paths. Perceptions about career satisfaction indicated that CNMs were moderately satisfied with overall career success but less satisfied with income and career ladders. This study serves as an important precursor to future research which could explore CNMs’ perceptions regarding pay equity as well as the intrinsic and extrinsic factors that are more critical at various junctures in their career paths. Results from the study also help to fill an existing gap in the dietetics and career path literature and will also assist the Academy of Nutrition and Dietetics and others in developing strategies to foster the career development of CNMs.
Keywords: clinical nutrition managers; dietetics; career paths; Nutrition (0570)